Pengaruh Media Pembelajaran Berbasis Augmented Reality terhadap Kemampuan Berpikir Simbolik Anak Usia 5-6 Tahun - Kencanawati, Inayah; Bachtiar, Muhammad Yusri; Herman; Lismayani, Angri (NANAEKE: Indonesian Journal of Early Childhood Education, 2024)
The research aims to determine the effect of augmented reality-based learning media on the symbolic thinking abilities of children aged 5-6 years at Raudhatul Jannah Kindergarten. The research approach used is a quantitative approach with a Quasi Experimental Design research type. The sample in this study was 20 group B children aged 5-6 years with 10 children as the experimental group and 10 children as the control group. The data collection techniques used in this research are observation, tests and documentation. The data analysis technique used was descriptive statistical analysis and non-parametric analysis using the Wilcoxon Sign Rank Test version 23. Based on the research results, it can be concluded that the symbolic thinking ability of children who were treated using augmented reality-based media in the experimental group was better than the control group. The results of data analysis showed that the average increase in the experimental group was 25.00, while in the control group it was 19.00. The test results show that sig. (2-tailed) 0.003 < 0.05 then H0 is rejected and H1 is accepted. So it can be concluded that augmented reality-based learning media influences the symbolic thinking abilities of children aged 5-6 years at Raudhatul Jannah Kindergarten.